2001
DOI: 10.1007/s11664-001-0156-2
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution in the Sn-Cu-Ni and Pb-Sn solder joints with Cu and Pt-Ag metallized Al2O3 substrate

Abstract: Special Issue PaperThe growth mechanism of intermetallics between solders and metallized substrates, after thermal aging, are investigated. The solders used in this study are unleaded Sn-Cu-Ni solder and eutectic Pb-Sn solder. The Pt-Ag/Al 2 O 3 , Cu block and the electroless Cu/Pt-Ag/Al 2 O 3 are employed as the metallized substrates. Microstructure evolution of the interfacial morphology, elemental, and phase distribution are probed with the aid of electron-probe microanalyzer (EPMA) and x-ray diffractometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…They reported that Ni on the substrate side could diffuse across the entire solder joint and formed the (Cu,Ni) 6 Sn 5 ternary phase on top of the Ni(V) UBM on the chip side during reflow cycles. However, Young et al [15] reported that two kinds of intermetallics (Cu 6 Sn 5 and Cu 3 Sn) are formed at a Sn-2.7 wt.% Cu-0.2 wt.% Ni/Cu interface, which is different from our result. The Cu-Ni binary system forms a complete solid solution.…”
Section: Resultscontrasting
confidence: 99%
“…They reported that Ni on the substrate side could diffuse across the entire solder joint and formed the (Cu,Ni) 6 Sn 5 ternary phase on top of the Ni(V) UBM on the chip side during reflow cycles. However, Young et al [15] reported that two kinds of intermetallics (Cu 6 Sn 5 and Cu 3 Sn) are formed at a Sn-2.7 wt.% Cu-0.2 wt.% Ni/Cu interface, which is different from our result. The Cu-Ni binary system forms a complete solid solution.…”
Section: Resultscontrasting
confidence: 99%
“…Therefore, many researchers have engaged in investigating the interface reactions between solder alloys and Cu substrate or other under bump metallization (UBM) layers [2][3][4][5]. -Cu 6 Sn 5 is the most often observed IMC formed at the Sn-base solder/Cu interface and has a hexagonal structure [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Sn-lead (Sn-Pb) solders are most prominent interconnect materials for soldering the electronic components with the circuit boards [1]. However, nowadays, the use of this solder is so far restricted due to the environmental and health concern [2][3][4].…”
Section: Introductionmentioning
confidence: 99%